Reviewer Acknowledgements - Williams, Richard (Journal of Agricultural Studies, 2021)
Journal of Agricultural Studies (JAS) would like to acknowledge the following reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether JAS publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 9, Number 1 Ahmed Mohamed Elbeltagi, Mansoura University, Egypt Ai-Ping Wu, Hunan Agricultural University, China Alessandra M. Lima Naoe, Federal University of Tocantins, Brazil Alexandra-Nadia Cirdei, Technical University of Civil Engineering of Bucharest, Romania Alexandru Ioan Apahidean, UASVM, Romania Ana Daniela Lopes, Universidade Paranaense, Brazil Anca-Luiza Stanila, ICPA, Romania Angel Ramon Sanchez Delgado, Universidade federal Rural do Rio de Janeiro, Brazil Arnaud Z. Dragicevic, IRSTEA, France Benard Kiplangat Rop, University of Nairobi, Kenya Cleber Duarte, University of Guararapes, Brazil Darwin Pangaribuan, University of Lampung, Indonesia Eben von Well, Agricultural Research Council, South Africa Eric Krawczyk, University of Michigan, USA Eric Owusu Danquah, CSIR-Crops Research Institute, Ghana Fábio Cassola, UNICAMP, Brazil Fernando Coelho Eugenio, Federal University of Santa Maria, Brazil Guitong Li, China Agricultural University, China Habu Saleh Hamisu, National Horticultural Research Institute, Nigeria Hedayatollah K. Soureshjani, Ferdowsi University of Mashhad, Iran Janerson Jose Coelho, Universidade Federal Rural de Pernambuco, Brazil João Manoel da Silva, Universidade Federal de Alagoas, Brazil Jorge A. López, University Tiradentes, Brazil Mahyar Gerami, Sana Institute of Higher Education, Iran María Elena Estrada Martínez, Universidad Metropolitana, Ecuador María Francisca Perera, ITANOA, EEAOC-CONICET, Argentina Mariana Esteves, Luiz de Queiroz College of Agriculture University of Sao Paulo, Brazil Md. Sadique Rahman, Sher-e-Bangla Agricultural University, Bangladesh Neha Jha, Massey University New Zealand, New Zealand Nkemkanma Vivian Agi, Rivers State University Port Harcourt, Nigeria Olga Mykhailenko, National University of Pharmacy, Ukraine Oscar Mitsuo Yamashita, Universidade do Estado de Mato Grosso, Brazil Raul Pașcalău, BUASVM, Romania Saiful Irwan Zubairi, Universiti Kebangsaan Malaysia (UKM), Malaysia Samir Neggaz, Université Oran, Algeria Sarir Ahmad, Abdul Wali Khan University, Pakistan Shakirudeen Abimbola Lawal, University of Cape Town, South Africa Shubha Kumari, ICAR-RCER, India Somaia Alkhair, Alzaeim Alazhari University, Sudan Sybelle Mesquita Silva, Universidade Federal de Alagoas, Brazil Toncho Gospodinov Penev, Trakia University, Bulgaria Utkarsh R. Moon, Mahatma Gandhi College of Science, India Wossenie Shibabaw Mebratie, Bahir Dar University, Ethiopia Zakaria Fouad Abdallah, National Research Centre, Egypt Zhao Chen, Clemson University, USA Richard Williams Editorial Assistant Journal of Agricultural Studies ————————————– Macrothink Institute 5348 Vegas Dr.#825 Las Vegas, Nevada 89108 United States Phone: 1-702-953-1852 ext.521 Fax: 1-702-420-2900 Email 1: jas@macrothink.org Email 2: jas@macrothink.com URL: http://jas.macrothink.org